2020
DOI: 10.37201/req/099.2019
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and etiology of vulvovaginal candidiasis in Spanish and immigrants’ women in Fuenlabrada (Madrid)

Abstract: Objectives. Vulvovaginal candidiasis (VVC) is a common vaginal infection. Risk factors include diabetes, antibiotic use and pregnancy. Candida albicans is the most common species identified but non-C. albicans species appear to be more commonly associated with VVC in some Asian and African countries. We had studied the distribution of Candida species in Spanish and immigrants’ women residents in Spain. Material and methods. Retrospective study of vaginal yeast cultures between 2015 and 2018. Results. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
4
0
6
Order By: Relevance
“…It provides data on an infection for which there are usually no accurate national or local data, and the magnitude of associations of the socio-demographic and sexual behavioural variables with VVC has been explored and quantified. To our knowledge, it is one of the few studies that has been developed in our context with similar objectives [ 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides data on an infection for which there are usually no accurate national or local data, and the magnitude of associations of the socio-demographic and sexual behavioural variables with VVC has been explored and quantified. To our knowledge, it is one of the few studies that has been developed in our context with similar objectives [ 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The socio-demographic profile of women diagnosed with VVC was found to correspond to a Spanish woman, who is a student, not in active employment, with a higher education, who is single, and under 30 years of age. A study conducted in Madrid reported more positive cultures for VVC in foreign women (28.5%) than in Spanish women (25.7%) [ 22 ], while López-Olmos et al [ 41 ] in Valencia reported the opposite (16.03% vs. 23.97%). As in our study, in none of these studies was the country of birth found to be statistically associated with infection.…”
Section: Discussionmentioning
confidence: 99%
“…En el mundo la prevalencia de CVV tiende a ser baja con 5,3 % en Alemania (13) y mayor en África con un 44,4 % en Nigeria ( 14) y en los países asiáticos con 32,7 % en India ( 15), 31,6 % en Dubái (1), 28,8 % en Nepal ( 16) y 26 % en Irán (17). Esta diferencia podría deberse a varias razones como los criterios de selección de las pacientes en los estudios, hábitos socioculturales, las condiciones rurales, factores de riesgo para la infección y la dinámica de la población local, lo que explica enormes disparidades en la tasa de prevalencia entre países (18). Un factor que determina el comportamiento epidemiológico de los agentes causales de las infecciones genitales en las mujeres es el abordaje sindromático recomendado por las guías de práctica clínica (19).…”
Section: Discussionunclassified
“…En el 2008 en México el tipo más frecuente de Vaginosis presentado en mujeres de edad fértil de 15 a 44 años fue de etiología bacteriana. Se identificó una prevalencia que oscila entre el (10-40%) (Aroca et al, 2020). Ocurriendo en más del (30%) de la población puede llevar a enfermedad inflamatoria pélvica y subsecuente a infertilidad, y susceptibilidad de parto pretérmino en pacientes gestantes (Zambrano-Loor et al, 2018).…”
Section: Introductionunclassified